Works Involving Marc Karsner and French Mathematicians - Escassut, Alain (Sarajevo Journal of Mathematics, 2024)
Works due to Marc Kasner are well known and famous in several domains. Here are short abstracts on only some domains Krasner's works: on hypergroups, ultrametric analysis and Hederic fields, mainly made with French mathematicians.